ATTEMPTS TO IMPROVE TEACHER PROFESSIONALISM THROUGH ACADEMIC SUPERVISION AT SDN 95 PEKANBARU - Amir Hakim Harahap (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper documents the improvement of teacher professionalism through academic supervision. Teacher professionalism has been widely scrutinized as one of the main issues in education. Because one of the components that determine student learning outcomes is the teacher. With academic supervision, teacher professionalism can be increased at the institutional level. Therefore, the implementation of academic supervision needs to be carried out systematically by supervisors so that the teachers can carry out their duties effectively and efficiently. The implementation of academic supervision needs to be directed to the attempts that provide opportunities for teachers to develop professionally. The research in this paper is School Action Research (PTS) using Kemmis and Mc. Taggart research design model. The research was conducted at SDN 95 Pekanbaru. The research subjects involved 27 teachers. Two cycles that reveal the results of the teacher's ability or understanding are increasing. The initial conditions’ percentage score in cycle I were 44.44%, 51.85%, 51.85%, and 44.44%. Subsequently, it increased significantly in cycle II, which were 100%, 92.59%, 88.88%, and 85.18%. Overall, teacher professionalism increased significantly. Based on this case, academic supervision helps teachers to develop their abilities in achieving the learning objectives, which have been set for their students.